Impact Evaluation Of Community-Led Total Sanitation In Sawla-Tuna-Kalba And Bole Districts In The Savannah Region - Adzaho, E. (University Of Ghana, 2022)
Background: Open defecation is a major public health issue because it is responsible for tremendous diarrhea and typhoid disease burden in the country. Objectives: This study aimed to assess the impact of community-led total sanitation (CLTS) on diarrhea and typhoid incidence in the Bole and Sawla-Tuna-Kalba districts, and further assess the changes in latrine coverage and open defecation-free (ODF) status. Methods: A single group-interrupted time-series design with a negative binomial regression model with robust standard error was used to determine the impact of the CLTS intervention. A pre and post-comparison was made on data gathered between January 2011 to December 2015, and January 2016 to December 2021. Data was coded, entered, and cleaned in MS Excel version 2019 and exported to Stata version 16 for analysis, and a p-value of <0.05 was considered statistically significant. Results: CLTS contributed to a one percentage point-reduction in diarrhea (aIRR 0.99, 95% CI: 0.98, 9.99; p<0.001) and a one percentage point reduction in Typhoid (aIRR 0.99, 95% CI: 0.97, 1.00; p-value <0.02) cases in Bole district. Typhoid incidence appeared to have increased in Sawla-Tuna-Kalba district by 2.0% post-intervention (aIRR 1.02, 95% CI: 1.01-1.04; p<0.001). Latrine coverage in Sawla-Tuna-Kalba and Bole district increased by 40.7% and 9.6% respectively post the intervention. About 98% and 43.0% of the communities in Sawla-Tuna-Kalba and Bole districts were respectively declared as open defecation free after the implementation of the intervention. Conclusion: Community-led total sanitation is a vital approach that helps to reduce the practice of open defecation and increase latrine coverage in rural communities. However, to ensure a good health outcome that will led to a reduction in typhoid and diarrhea incidence, continuous monitoring and education must be carried out to ensure that communities practice good hygiene and do not revert to open defecation.
MSc. Public Health Monitoring & Evaluation
Keywords: The Savannah Region; Bole Districts; Sawla-Tuna-Kalba; Community-Led Total Sanitation